EFFECT OF SOWING DATE AND NORMS ON LEAF AREA OF SOYBEAN VARIETIES - Dusmatova Lola Xashimovna; Khalikov Bahodir Meylikovich (Modern American Journals, 2025)
This article presents data on the effect of different sowing dates and norms on the surface area of the soybean varieties "Madad" and "Sevinch" and their analysis. It is reported that when the sowing norm of soybean varieties is increased by 15 kg compared to 45 kg per hectare, the leaf area is increased by 240-340 cm2, and when it is increased by 30 kg, the leaf area is increased by 470-780 cm2, and when the sowing date is delayed by 10 days compared to the period of 25.04-30.04, the leaf area is reduced by 532-785 cm2, and when it is delayed by 20 days, the leaf area is reduced by 1220-1375 cm2.
Keywords: Sowing dates, sowing norms, leaf area, soybean, variety.